2013
DOI: 10.1109/tbme.2013.2257769
|View full text |Cite
|
Sign up to set email alerts
|

Motion Correction for MR Cystography by an Image Processing Approach

Abstract: Magnetic resonance (MR) cystography or MR-based virtual cystoscopy is a promising new technology to evaluate the entire bladder in a fully non-invasive manner. It requires the anatomical bladder images be acquired at high spatial resolution and with adequate signal-to-noise ratio (SNR). This often leads to a long-time scan (> 5 minutes) and results in image artifacts due to involuntary bladder motion and deformation. In this paper, we investigated an image-processing approach to mitigate the problem of motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This observation is consistent with our previous studies reported in [13], [14]. Furthermore, with respect to comparing different methods for dynamic scans registration, the presented α –registration approach outperformed the well–known mutual information approach in terms of RMSE/CC for phantom studies and in terms of SNR of the bladder wall for patient studies.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation is consistent with our previous studies reported in [13], [14]. Furthermore, with respect to comparing different methods for dynamic scans registration, the presented α –registration approach outperformed the well–known mutual information approach in terms of RMSE/CC for phantom studies and in terms of SNR of the bladder wall for patient studies.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Our previous work has shown that retrospective motion correction (RMC) is a promising image processing approach for MR imaging of the moving, expanding, and deforming bladder wall [13], [14]. In this study, we further investigate the effect of selecting an effective image registration method for the RMC in bladder MR images.…”
Section: Introductionmentioning
confidence: 99%
“…However, the information in 2D image slices is non-continuous owing to slice gaps. Hence, improvements in bladder wall imaging call for enhancement of contrast and SNR and reduced susceptibility to artifacts 79 during image acquisition and 3D reconstruction.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…The protection strategy of VSC-HVDC system has been investigated in Refs. [ 21 22 ]. Yuan et al [ 23 ] studied the unbalanced three-phase control strategy of VSC-HVDC system.…”
Section: Introductionmentioning
confidence: 99%